UPAYA MENINGKATKAN HASIL BELAJAR MATEMATIKA MELALUI PENERAPAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING MATERI UKURAN TENDENSI SENTRAL PADA SISWA KELAS XII IPA SMA NEGERI 1 DEKAI - ISTIN YULIATIN (SECONDARY: Jurnal Inovasi Pendidikan Menengah, 2023)
This study aims to find out how efforts to improve mathematics learning outcomes through the Problem Based Learning learning model apply material concentration measures to class XII IPA students at SMA Negeri 1 Dekai in the 2022/2023 academic year. This study used the Classroom Action Research (CAR) method. Based on the results of the research and discussion, it can be concluded that efforts to improve mathematics learning outcomes can be carried out through the application of the Problem Based Learning model for material on measures of central tendency at Dekai 1 Senior High School in the 2022/2023 Academic Year. Utilization of the Problem Based Learning learning model can help students study knowledge and be able to create learning situations that are more conducive, effective, interactive, and fun. In cycle 2 students are getting used to solving problems when discussing with Problem Based Learning models, so there is no need to explain too much. - long-winded as in cycle 1. Learning outcomes increased as seen from the level of completeness classically in each cycle there was an increase, in cycle 1 students who achieved KKM 65 were 14 students or 46.67% while in cycle 2 students who achieved KKM were 26 students or by 86.67%. Even though the scores obtained by the students were not high and most of them were only able to reach the KKM, there was an increase in the average and the range. In cycle 1 the average student only reached 53.33 with a range of 80, while in cycle 2 the average student reached 64.83 with a range of 85 ABSTRAKPenelitian ini bertujuan untuk mengetahui bagaimana upaya meningkatkan hasil belajar matematika melalui model pembelajaran Problem Based Learning materi penerapan ukuran pemusatan data pada siswa kelas XII IPA SMA Negeri 1 Dekai Tahun Pelajaran 2022/2023. Penelitian ini menggunakan metode Penelitian Tindakan Kelas (PTK). Berdasarkan hasil penelitian dan pembahasan, dapat di simpulkan bahwa upaya meningkatkan hasil belajar matematika dapat dilakukan melalui penerapan model Problem Based Learning materi ukuran tendensi sentral di SMAN 1 Dekai Tahun Pelajaran 2022/2023. Pemanfaatan model pembelajaran Problem Based Learning dapat membantu siswa dalam mengkaji ilmu serta mampu menciptakan situasi pembelajaran yang lebih kondusif, efektif, interaktif, dan menyenangkan pada siklus 2 siswa sudah mulai terbiasa menyelesaikan masalah ketika diskusi dengan model Problem Based Learning, sehingga tidak perlu dijelaskan terlalu bertele-tele seperti pada siklus 1. Hasil belajar meningkat dilihat dari tingkat ketuntasan secara klasikal pada tiap siklus mengalami peningkatan, pada siklus 1 siswa yang mencapai KKM 65 sebanyak 14 siswa atau sebesar 46,67% sedangkan pada siklus 2 siswa yang mencapai KKM sebanyak 26 siswa atau sebesar 86,67%. Meskipun nilai yang diperoleh siswa tidak tinggi dan sebagian besar hanya mampu mencapai KKM, namun terjadi peningkatan rata-rata dan jangkauannya. Pada siklus 1 rata-rata siswa hanya mencapai 53,33 dengan jangkauan 80, sedangkan pada siklus 2 rata-rata siswa mencapai 64,83 dengan jangkauan 85